2016
DOI: 10.1111/jir.12251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous aerobic vs. interval training on selected anthropometrical, physiological and functional parameters of adults with Down syndrome

Abstract: Interval training and CAT can both be pursued by adults with DS to positively impact on various parameters of anthropometry, fitness and functional ability, with IT more appropriate for improving body weight and aerobic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
184
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(196 citation statements)
references
References 66 publications
(163 reference statements)
4
184
0
8
Order By: Relevance
“…Rikli and Jones (2013) defined functional fitness as having the physical capacity to perform normal everyday activities safely and independently without undue fatigue. Fortunately, a vast number of research studies have shown that adults with DS can improve their functional fitness through structured activities of aerobic (Carmeli et al 2002b;Mendonca and Pereira 2009;Boer and Moss 2016a), resistance (Cowley et al 2011), combined aerobic and resistance (Mendonca et al 2013) or balance (Tsimaras and Fotiadou 2004) training. Being functionally fit is important for all populations, but even more so for populations at risk of deteriorating functional capacity such as the elderly, persons with disabilities and those with chronic medical conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rikli and Jones (2013) defined functional fitness as having the physical capacity to perform normal everyday activities safely and independently without undue fatigue. Fortunately, a vast number of research studies have shown that adults with DS can improve their functional fitness through structured activities of aerobic (Carmeli et al 2002b;Mendonca and Pereira 2009;Boer and Moss 2016a), resistance (Cowley et al 2011), combined aerobic and resistance (Mendonca et al 2013) or balance (Tsimaras and Fotiadou 2004) training. Being functionally fit is important for all populations, but even more so for populations at risk of deteriorating functional capacity such as the elderly, persons with disabilities and those with chronic medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors explained that functional fitness refers to having adequate strength, balance, mobility and endurance to execute essential tasks efficiently and effortlessly. Aerobic activities that are primarily used included modalities consisting of running (Tsimaras et al 2003;Boer and Moss 2016a), cycling (Mendonca and Pereira 2009) and rowing (Varela et al 2001). Fortunately, a vast number of research studies have shown that adults with DS can improve their functional fitness through structured activities of aerobic (Carmeli et al 2002b;Mendonca and Pereira 2009;Boer and Moss 2016a), resistance (Cowley et al 2011), combined aerobic and resistance (Mendonca et al 2013) or balance (Tsimaras and Fotiadou 2004) training.…”
Section: Introductionmentioning
confidence: 99%
“…Pessoas com SD que praticam exercícios apresentam melhor aptidão física, devido essa prática contribuir na melhora do condicionamento cardiorrespiratório, força muscular e peso corporal [10][11][12][13][14][15][16][17][18][19] , porém essa população apresenta pouca participação em programas de exercícios por razões multifatoriais como falta de motivação, inclusão social, programas e supervisão adequados 14 . Em geral, apenas 50% das pessoas que ingressam em um programa de exercícios físicos permanecem nele por mais de seis meses 103 .…”
Section: Discussionunclassified
“…Além disso, há relação inversa entre mortalidade e estilo de vida que inclui a prática de exercícios no cotidiano 81,82 . Em todos os estudos observou-se que a prática de exercícios físicos trouxe benefícios às pessoas com SD, como melhora do condicionamento cardiorrespiratório e da força muscular [10][11][12][13][14][15][16][17][18][19] . O equilíbrio postural mostrou diferença para o domínio I Transições -ajustes posturais antecipatórios (p=0,016) e no escore total da avaliação (p=0,02).…”
Section: Exercício Físico E Síndrome De Downunclassified
See 1 more Smart Citation